Proposed Design Improvement In Process Flow and Form Of Process Change Request at PT. ABC - Ken Warsy Triastuti (Widya Teknik, 2021)
PT. ABC is a corporation in the automotive manufacturing industry. In corporation's production, PT. ABC supplies goods from several suppliers. Quality management of suppliers and supply goods is needed by PT. ABC to obtain supplies according to the standards set by PT. ABC. The Process Change Request (PCR) is a requisite process for the standard change of supply items covering 4M (man, machine, method, and material). The process flow and form of Process Change Request have been standardized and listed on the Supplier Quality Assurance Manual (SQAM). The Supplier Quality Assurance Manual (SQAM) is the requirement document as a guide to the quality of parts and components, a corporation's internal quality assurance, and a policy for suppliers. In the process flow and form of PCR has been found a problem of inconsistency between the ideal time and the actual time of the PCR's approval phase which hampered the supply of PT. ABC caused by waste. In this study, the researcher proposed the improvement design to the process flow and form of PCR by applying the kaizen concept approach (continuous improvement) using the "plan" step of The PDCA cycle method (plan-do-action) and the fishbone diagram.